Analysis and identification of Pseudomonas sp. and molds on dried anchovy (Stelophorus sp) products produced by the people of Toniku Village, Halmahera Barat Regency, North Maluku Province - Ruslan A. Daeng; Azis Husen (Sekolah Tinggi Ilmu Pertanian Wuna, 2019)
This research was conducted to determine the characteristics of Pseudomonas sp. and mold on dried anchovies. The sample in this study was obtained from the fishing community of Toniku Village, West Halmahera Regency, North Maluku Province. The stages carried out in this study were 3 (three) stages, namely the sample preparation stage, the analysis phase and the identification stage of Pseudomonas sp. and mold. The results showed that the characteristics of the Total Plate Count (TPC) of dried anchovy in the Toniku Village obtained a different composition from each other, with the highest log Total Plate Count (TPC) obtained, namely 5.5 or 3.2 x 105 Cfu/g or 320.000 cells bacteria, while the lowest Total Plate Count (TPC) log was obtained, 2.5 or 3.1 x 102 Cfu/g or 310 bacterial cells and for total Pseudomonas bacteria from the three sampling locations no growth was found. The highest total log fungi were obtained ie 5.6 or 3.7 x 105 Cfu/g or 370.000 mold cells, while the lowest total log fungi were obtained which were 2.4 or 2.6 x 102 Cfu/g or 260 mold cells